Arterial oxygen saturation in healthy Mexican full-term newborns at different altitudes above sea level - Moisés Mier-Martínez; Luis García-Benítez; Verónica Santiago-Vázquez; Orlando Tamariz-Cruz (Boletín Médico del Hospital Infantil de México, 2023)
Background: Arterial oxygen saturation (SaO2) values are used to make clinical decisions that might change a patient’s prognosis, and it has been proposed as the fifth vital sign. This study aimed to determine the variation of SaO2 at different altitudes above sea level (ASL) in healthy Mexican full-term newborns. Methods: From July 2018 to June 2019, a cross-over study was conducted in six hospitals at different altitudes ASL in Mexico. SaO2 was measured in 4015 newborns after the first 24 h of birth and before leaving the hospital using pulse oximetry. We analyzed three groups: < 250 m ASL (group 1), 1500 m ASL (group 2), and 2250 m ASL (group 3). Results: The mean SaO2 was 97.6 ± 1.8%. For group 1, mean oxygen saturation was 98.2 ± 1.9%; for group 2, 96.7 ± 1.9%, and for group 3, 96.0 ± 2.1%. A statistically significant difference was observed among the groups (p < 0.001), and this difference was higher between groups 1 and 2 (1.5%, p < 0.001). Linear regression analysis showed a decrease in oxygen saturation of 1.01% for every 1000 m ASL. Conclusions: We demonstrated a statistically significant reduction in SaO2 levels at higher altitudes. This observation can be relevant for clinical decision-making based on pulse oximetry such as critical congenital heart disease screening in Mexico, where more than half of the population lives above 1500 m ASL.